Komputerisasi sebagai Media Karya Tipografi Eksperimental - Setiautami, Dria (Humaniora, 2010)
Typography is one of the elements design, which one designer can make their own style with it. As we know, the computer era move so fast, so we have to know how we get the basic visual from the personal computer. The fact is the shape of typography can’tbe changes, that’s why we have to know how to change them and get another expression for the form. With the personal computer we can do the exerimentala of typography with the rules and breaking the rules.